CD276 is a promising biomarker for the prognosis of clear cell renal cell carcinoma - Yan‐Hang Yu; Jian‐Hao Xu; Hao Chen; Yu‐Xin Lin; Jun Ou‐Yang; Zhi‐Yu Zhang (Kaohsiung Journal of Medical Sciences, 2024)
Abstract This study aimed to investigate the role of cluster of differentiation 276 (CD276) in evaluating the prognosis of clear cell renal carcinoma (ccRCC) and to build a nomogram for predicting ccRCC progression post‐surgery. Using data downloaded from The Cancer Genome Atlas (TCGA) database, we constructed a Kaplan–Meier (KM) curve depicting the relationship between CD276 expression levels and the progression‐free interval (PFI) in 539 ccRCC cases. We further validated this by plotting a KM curve of the relationship between CD276 expression levels and PFI in 116 ccRCC patients from our hospital. Using clinical data collected from 116 patients, we identified independent risk factors affecting postoperative PFI in patients with ccRCC through univariate and multivariate COX analyses and created a nomogram for visual representation. Both TCGA and clinical data revealed a negative correlation between the expression levels of CD276 and PFI (p < 0.05). Univariate COX analysis revealed that the prognostic nutritional index, neutrophil‐to‐lymphocyte ratio, platelet‐to‐lymphocyte ratio, systemic inflammatory index, World Health Organization grading, tumor diameter, CD276 expression levels, T stage, and N stage were related to PFI (p < 0.05). Furthermore, multivariate COX analysis indicated that tumor diameter and CD276 expression levels were independent risk factors for postoperative PFI in patients with ccRCC (p < 0.05). The calibration curve of the established nomogram exhibited a slope close to 1, with a Hosmer–Lemeshow goodness‐of‐fit test result of 2.335 and a p‐value of 0.311. In patients with ccRCC, a negative correlation was noted between tumor CD276 expression and PFI. The larger the tumor diameter and the higher the tumor CD276 expression level, the shorter is the PFI.